Fungsi Bahasa Dalam Wacana Lisan Pidato Puan Maharani Pada Acara Hari Bung Karno - Nadia Azkal Uyun; Khusnul Khotimah (Widyantara, 2023)
This research aims to analyze the functions of language used in Puan Maharani's speech during the Bung Karno Day, which was uploaded three months ago on the Liputan6 YouTube channel. The speech is considered a significant example of oral discourse in the context of commemorating Bung Karno Day. This study utilizes a discourse analysis approach with M.A.K. Halliday's (1973) theory of language functions, including instrumental function, regulatory function, representational function, interactional function, personal function, heuristic function, and imaginative function. The research method employed is qualitative descriptive. The data source consists of the video of Puan Maharani's speech on the Liputan6 YouTube channel. Data collection involved listening, transcribing the video into text, and note-taking. The results of the study indicate that in Puan Maharani's speech, language is used to convey essential messages related to the commemoration of Bung Karno Day. The dominant language function used is the representational function compared to other functions. This is because the speaker conveys facts while showing respect to state officials and political party leaders. This analysis provides a better understanding of the role of language in oral discourse in the context of historical and cultural commemorations. The implications of these findings can also contribute to the development of studies on language functions in a broader oral discourse context. Penelitian ini bertujuan untuk menganalisis fungsi bahasa yang digunakan dalam pidato Puan Maharani saat hari Bung Karno yang diunggah tiga bulan lalu oleh kanal YouTube Liputan6. Pidato tersebut dianggap sebagai contoh signifikan dari wacana lisan dalam konteks peringatan Hari Bung Karno. Penelitian ini menggunakan pendekatan analisis wacana dengan teori fungsi bahasa M.A.K Halliday (1973) yang meliputi, fungsi instrumental, fungsi regulasi, fungsi representasional, fungsi interaksional, fungsi perorangan, fungsi heuristik, dan fungsi imajinatif. Metode penelitian yang digunakan ialah deskriptif kualitatif. Sumber data berupa video pidato Puan Maharani di kanal YouTube Liputan6. Pengambilan data dikumpulkan melalui mendengarkan, transkrip video ke teks, dan mencatat. Hasil penelitian menunjukkan bahwa dalam pidato Puan Maharani, bahasa digunakan untuk menyampaikan pesan-pesan penting terkait dengan peringatan Hari Bung Karno. Fungsi bahasa yang dominan digunakan yakni fungsi bahasa representasi dibandingkan fungsi-fungsi yang lain. Hal ini dikarenakan penutur banyak menyampaikan fakta melalui rasa hormat kepada para petinggi negara dan partai politik. Analisis ini dapat memberikan pemahaman yang lebih baik tentang peran bahasa dalam wacana lisan dalam konteks peringatan sejarah dan budaya. Implikasi dari temuan ini juga dapat memberikan kontribusi pada pengembangan studi tentang fungsi bahasa dalam wacana lisan yang lebih luas.